Examining some of the Students’ Challenges and Alternative Conceptions in Learning about Acid-base Titrations - Issa I. Salame; Adrianny Montero; Dani Eschweiler (Universitas Islam Indonesia, 2022)
Chemical equilibria, including acid-base equilibria, play a significant role in the learning of general chemistry. Acid-base reactions as well as acidity and basicity concepts and their relationship to titrations are an important part of any general chemistry course, and students have difficulties understanding these concepts. The purpose of this research project is to examine some of the challenges and alternative conceptions that students face in learning about acid-base titrations. A Likert-type survey with open-ended questions were used to assess the understanding of 110 participants. The investigation took place at a public, urban, and minority-serving institute. Our data suggest that students struggle with learning about acid-base titration problems and concepts. They rely on algorithmic problem solving, rote- learning, plugging into equations, and calculator use when approaching acid-base titration problems instead of developing their conceptual understanding and meaningful learning of the concepts. Additionally, our data support the notion that development of conceptual understanding of acid-base titration is important for students’ learning. Furthermore, our research data suggest that students have difficulties with understanding and visualizing what is taking place at the microscopic level during acid-base titration reactions. Instructors should consider teaching strategies that include leaning about and interrelating the symbolic, macroscopic, and microscopic levels of representations which can promote learning and deeper understanding of abstract chemical concepts. We recommend that instructors explicitly address and relate the three levels of representation in their teaching of chemistry concepts. Keywords: chemistry education research, acid-base titration, challenges